2012
DOI: 10.1007/s13238-012-2068-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct lineage conversion: induced neuronal cells and induced neural stem cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“… [82] , [83] ). While direct reprogramming of neurons and cardiomyocytes have been extensively discussed elsewhere [84] , [85] , [82] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [80] , [98] , [81] , [83] , we will focus on studies that revealed different miRNAs with a role in mediating direct cell reprogramming towards neurons and cardiomyocytes.…”
Section: Mirnas: Master Orchestrators Of Gene Expressionmentioning
confidence: 99%
“… [82] , [83] ). While direct reprogramming of neurons and cardiomyocytes have been extensively discussed elsewhere [84] , [85] , [82] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [80] , [98] , [81] , [83] , we will focus on studies that revealed different miRNAs with a role in mediating direct cell reprogramming towards neurons and cardiomyocytes.…”
Section: Mirnas: Master Orchestrators Of Gene Expressionmentioning
confidence: 99%
“…In addition, Torper also found that mouse astrocytes could be directly reprogrammed into neurons with nuclei expression in vivo. Doxycycline-regulated lentiviruses (LVs) were chosen as vectors to deliver the neuron-related factor combination of Ascl1, Brn2a, and Mytl1 (Pfisterer et al, 2011;Shi and Jiao, 2012). To determine the effect of doxycycline, these vectors were used to activate specific neuronal genes for the conversion process in vivo (Grealish et al, 2010;Pang et al, 2011).…”
Section: Conversion Into Neuronsmentioning
confidence: 99%
“…Following the publication of methods to harness and propagate iPSCs, other methods related to direct conversion from fibroblasts to neuronal cells by defined transcription factors have been reported ( Vierbuchen et al, 2010 ; Yang et al, 2013 ). The neural lineage is composed of induced neuronal (iN) cells, induced neural progenitor cells (iNPCs), and induced NSCs (iNSCs; Yang et al, 2011 ; Abdullah et al, 2012 ; Corti et al, 2012 ; Shi and Jiao, 2012 ). Moreover, iPSC-derived MSCs (iPSC–MSCs) were identified ( Jung et al, 2012 ).…”
Section: Possibility Of Advanced Msc Therapies As a Solution Of Questmentioning
confidence: 99%